Characteristics of metabolic syndrome in the servicemen with erosive esophagitis in wartime conditions - L.M. Mosiychuk; O.M. Shevtsova; O.M. Tatarchuk; O.P. Petishko (Gastroenterologìa)
Background. Among the well-known factors contributing to the prevalence of erosive esophagitis, the leading one is an increase in the number of individuals with obesity and insulin resistance. The assessment of metabolic syndrome in the servicemen of the Armed Forces of Ukraine with erosive esophagitis in wartime conditions is of particular importance, as the effectiveness of their professional activities depends on it. The purpose of the study: to evaluate the body composition and insulin resistance in the servicemen of the Armed Forces of Ukraine with erosive esophagitis, taking into account the level of the stress index, exhaustion and adaptative capacity of the body. Materials and methods. The study included 24 men aged 33 to 57 years, the average age was (42.7 ± 2.1) years. All military personnel were assessed for maladjustment, increased cardiovascular risk, anxiety, and fatigue using the cardiorhythmography method based on the analysis of heart rate variability on the CONTEC8000GW system. Body composition was assessed using Tanita MC-780МА (Japan) scales-analyzers whose mechanism is based on the technique of bioimpedance analysis with computer processing. Insulin resistance was evaluated using the HOMA-IR index, for the calculation of which the level of insulin was determined by enzyme-linked immunosorbent assay systems of the Xema company (Ukraine) on the Stat Fax 303 Plus analyzer (USA). Results. According to precise diagnostics, half of the servicemen of the Armed Forces of Ukraine with erosive esophagitis were diagnosed with vegetative imbalance, which was manifested by an increase in the stress index in 37.5 % of cases, a disruption or violation of adaptation in 25.0 %, and exhaustion of the body in 54.2 % of cases. The HOMA-IR index was 1.5 times higher (p = 0.006) compared to that of the control group. 37.5 % of the servicemen of the Armed Forces of Ukraine with erosive esophagitis showed signs of metabolic syndrome. Correlation analysis revealed relationship of heart rate variability with body composition indicators (body mass index, fat mass, and amount of visceral fat). In addition, an increase in insulin resistance is associated with an increase in the stress index and cardiovascular risk, as well as a decrease in the adaptive capacity of the body and its exhaustion. Conclusions. The correlations found between indicators of heart rate variability, insulin resistance and body composition will allow for the development of a personalized approach to the management of the servicemen of the Armed Forces of Ukraine with erosive esophagitis.